The influence of corporate social responsibility disclosure and good corporate governance mechanisms on stock returns with financial performance as a moderating variable in Indonesia - William, William; Bambang Subiyanto (Jurnal Ekonomi, 2024)
Stakeholders believe that corporate social responsibility (CSR) activities and corporate governance practices can enhance a company's stock returns. Additionally, a company's financial performance can attract investor interest in investing their capital in that company. This study aims to obtain empirical evidence on the influence of CSR disclosure and good corporate governance (GCG) mechanisms on stock returns, as well as to understand the moderating role of financial performance in the relationship between CSR disclosure, GCG, and stock returns. The research was empirically conducted on companies listed in the IDX80 index at the Indonesia Stock Exchange from 2018 to 2022. Data analysis was performed using WarpPLS 8.0 software with 115 samples obtained through purposive sampling. The results of this study indicate that there is no direct influence of CSR disclosure and GCG mechanisms on stock returns. Investors do not yet consider CSR disclosure and GCG mechanisms in companies as crucial factors for the returns they obtain. However, financial performance strengthens the relationship between CSR disclosure, GCG, and stock returns, with respective significances of P-Value = 0.02 & 0.04, both less than 0.05. Good financial performance of a company further reinforces investors' desire to invest in companies with strong CSR and GCG practices.